Towards enhancing unsupervised anomaly detection by improving complexity, dimensionality and class-boundary properties - Babaei, Kasra (2022)
Any observation that follows a pattern other than the expected one, i.e., the normal behaviour, is considered abnormal behaviour (also known as an anomaly). Abnormal behaviour is witnessed in various areas— for instance, a previously unseen high temperature during winter in a naturally cold environment.